2018
DOI: 10.1186/s13075-017-1502-y
|View full text |Cite
|
Sign up to set email alerts
|

Are we there yet? An update on transitional care in rheumatology

Abstract: Significant progress has been made in the understanding of transitional care in rheumatology over the last few decades, yet universal implementation has not been realised and unmet needs continue to be reported. Possible explanations for this include lack of evidence as to which model is most effective; lack of attention to the multiple dimensions, stakeholders and systems involved in health transitions; and lack of consideration of the developmental appropriateness of transition interventions and the services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Demographic data, disease duration, and comorbid nonrheumatic conditions were collected from patients’ charts. An active joint count and a physician global assessment, a reliable, validated outcome used to describe disease activity in these patients (11), were also collected on each patient.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic data, disease duration, and comorbid nonrheumatic conditions were collected from patients’ charts. An active joint count and a physician global assessment, a reliable, validated outcome used to describe disease activity in these patients (11), were also collected on each patient.…”
Section: Methodsmentioning
confidence: 99%
“…Factors key to optimizing transition in patients with chronic health conditions include starting transition programs in early adolescence, co‐managing/coordinating care between pediatric and adult teams, sharing medical records, and providing education on self‐management and advocacy (11,12). Previous literature indicates that more than 50% of adolescents aged 12‐18 years with a variety of chronic health conditions lack basic skills to manage their own health (13).…”
Section: Introductionmentioning
confidence: 99%
“…A strength of this study was its support of the need for multi-systemic and multi-perspective research (McDonagh and Farre, 2018), by bringing together a range of perspectives across different organizational systems: YP and parents before and following transition, child and adult services, and commissioning organisations. Our patient sample age range was broad in recognition of transition as an extended process encompassing different developmental stages (Rapley et al, 2019).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In the transitional literature, an extensive amount of studies reported on specific patient groups such as ADs with rheumatic musculoskeletal disease (RMD) or childhood cancer survivors. [19][20][21] Although patients with MO might have certain disease-related problems in common with these group of patients, there are also specific MO-related problems and complications that could affect the study outcome. Important factors in this are the lifelong risk of malignant degeneration in MO, the multiple surgical procedures that are often necessary throughout life and the fact that in most cases, one parent has the same disease.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%